Spinal anaesthesia in a case of kyphoscoliosis - Kokane, Deepak Mahadeo; Hingole, Pradnya (International Journal of Advances in Medicine, 2017)
Kyphoscoliosis is forward and lateral bending of the spine commonly affecting the dorsal and lumbar spine. Spinal deformities are likely to be associated with physiologic derangements in cardiac and pulmonary function and may cause difficulties with both tracheal intubation and regional anaesthesia. Due to problems associated with respiratory system, spinal anaesthesia is used widely, though technically difficult. We present a case of thoracolumbar kyphoscoliosis posted for cystolithotomy successfully managed with spinal anaesthesia.